The genetic contribution of the X chromosome in age-related hearing loss - Naderi, Elnaz; Cornejo-Sanchez, Diana M.; Li, Guangyou; Schrauwen, Isabelle; Wang, Gao T.; Dewan, Andrew T.; Leal, Suzanne M. (Frontiers in Genetics, 2023)
Age-related (AR) hearing loss (HL) is the most common sensory impairment with heritability of 55%. The aim of this study was to identify genetic variants on chromosome X associated with ARHL through the analysis of data obtained from the UK Biobank. We performed association analysis between self-reported measures of HL and genotyped and imputed variants on chromosome X from ~460,000 white Europeans. We identified three loci associated with ARHL with a genome-wide significance level (p< 5x10-8), ZNF185 (rs186256023, p = 4.9x10-10) and MAP7D2 (rs4370706, p = 2.3x10-8) in combined analysis of males and females, and LOC101928437 (rs138497700, p = 8.9x10-9) in the sex-stratified analysis of males. In-silico mRNA expression analysis showed MAP7D2 and ZNF185 are expressed in mice and adult human inner ear tissues, particularly in the inner hair cells. We estimated that only a small amount of variation of ARHL, 0.4%, is explained by variants on the X chromosome. This study suggests that although there are likely a few genes contributing to ARHI on the X chromosome, the role that the X chromosome plays in the etiology of ARHL may be limited.